College Algebra - Perez, Angelita P.; Ymas, Jr., Sergio E. (Manila, Philippines : Sta. Monica Printing Corporation, 2002)
The book offers a comprehensive treatment of all materials normally introduced under the title college algebra to let the students savor the true contents of the subject. The contents of algebra may be grouped into 3 divisions: algebraic expressions, equations and inequalities and optional topics.
Chapter 1. Sets and numbers -- Chapter 2. Polynomials -- Chapter 3. Special product and factoring -- Chapter 4. Fractions -- Chapter 5. Exponents and radicals -- Chapter 6. Relations and functions -- Chapter 7. Linear equations and word problems -- Chapter 8. Quadratic equations and word problems -- Chapter 9. Inequalities -- Chapter 10. Systems of linear equations and word problems -- Chapter 11. Polynomial equations -- Chapter 12. Determinants -- Chapter 13. Systems involving quadratic equations and word problems -- Chapter 14. Proportions and variations -- Chapter 15. The binomial theorem -- Chapter 16. Progressions -- Chapter 17. Partial fractions.
Includes bibliographical references.
Keywords: ALGEBRA -- MATHEMATICS